Reliability Prediction of the Measurement Unit for Smart Meter Based on GJB/Z 299C - HUANG You-peng; LU Tao; DANG San-lei; CHEN Liang (Journal of Harbin University of Science and Technology, 2021)
To improve the reliability of domestic smart meter, the reliability prediction is needed during the design phase of smart meter. For the measurement unit, the reliability prediction method is given on GJB/Z299C. The integrated circuits or electronic components are grouped according to the circuit diagram designed. The corresponding reliability information diagram is designed on the categories and GJB/Z299C. The failure rate of each component can be calculated by combining engineering application with reliability information diagrams. Finally, the failure rate of measurement unit can be deduced. The practice results show that the method is feasible and is worth applying widely.